2001
DOI: 10.1074/jbc.m101985200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine 38 in p65/NF-κB Plays a Crucial Role in DNA Binding Inhibition by Sesquiterpene Lactones

Abstract: Sesquiterpene lactones (SLs) have potent antiinflammatory properties. We have shown previously that they exert this effect in part by inhibiting activation of the transcription factor NF-B, a central regulator of the immune response. We have proposed a molecular mechanism for this inhibition based on computer molecular modeling data. In this model, SLs directly alkylate the p65 subunit of NF-B, thereby inhibiting DNA binding. Nevertheless, an experimental evidence for the proposed mechanism was lacking. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
307
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(327 citation statements)
references
References 47 publications
13
307
1
6
Order By: Relevance
“…Because the effects of TQ could be reversed by reducing agent, it is possible that this agent modifies a cysteine residue in p65. These results are consistent with those previously reported from our laboratory and others with caffeic acid phenethyl ester (37), plumbagin (38), and sesquiterpene lactone parthenolide (40). A Cys 38 residue has been identified in p65 subunits of NF-nB that is crucial for DNA binding (40).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Because the effects of TQ could be reversed by reducing agent, it is possible that this agent modifies a cysteine residue in p65. These results are consistent with those previously reported from our laboratory and others with caffeic acid phenethyl ester (37), plumbagin (38), and sesquiterpene lactone parthenolide (40). A Cys 38 residue has been identified in p65 subunits of NF-nB that is crucial for DNA binding (40).…”
Section: Discussionsupporting
confidence: 83%
“…It has been reported that the cysteine residue located at position 38 in p65 is highly susceptible to various agents (38)(39)(40). Whether Cys 38 is a target for TQ was investigated.…”
Section: Tq Inhibits Tnf-induced Nuclear Translocation Of P65mentioning
confidence: 99%
“…Interestingly, NF-κB pathway inhibitors, including PTL, PDTC and DETC, were found to preferentially inhibit MCF7 sphere cell proliferation over parental MCF7 cells. PTL is a compound extracted from Tanacetum parthenium [53] and is known to inhibit the NF-κB pathway by preventing IkBa degration [54], inhibiting IkB kinase b [55] and alkylating of p65 [56]. PDTC and DETC are known to be antioxidants which inhibit the NF-κB pathway through blocking activation of nuclear factor kappa B (NF-kappa B) [33] and also inhibiting the IKK activity [57] and IκB-κ [58].…”
Section: Discussionmentioning
confidence: 99%
“…Some SLs can directly inhibit NF-kB DNA binding, primarily through interaction with Cys-38 in the DNA-binding loop of RelA (Garcı´a-Pin˜eres et al, 2001, 2004. Most SLs can also inhibit DNA binding by p50 and c-Rel through an analogous Cys residue in the DNA-binding loop, and mutations of this Cys residue to Ser generally make p50, RelA or c-Rel refractory to inhibition by such thiol-reactive compounds.…”
Section: Inhibitors Of Nf-kb Dna Bindingmentioning
confidence: 99%